2007
DOI: 10.1210/en.2007-0017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Central Melanocortin Signaling by Interleukin-1β

Abstract: Anorexia and involuntary weight loss are common and debilitating complications of a number of chronic diseases and inflammatory states. Proinflammatory cytokines, including IL-1 beta, are hypothesized to mediate these responses through direct actions on the central nervous system. However, the neural circuits through which proinflammatory cytokines regulate food intake and energy balance remain to be characterized. Here we report that IL-1 beta activates the central melanocortin system, a key neuronal circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 42 publications
6
119
2
3
Order By: Relevance
“…These observations suggest that leptin sensitivity, which plays an important role in protecting against dietinduced obesity by suppressing appetite [39], is increased in Il1ra −/− mice. In this regard, it is interesting that leptin signalling in the CNS regulates energy expenditure via activation of the SNS, leading to BAT-like differentiation of WAT [40].…”
Section: Discussionmentioning
confidence: 78%
“…These observations suggest that leptin sensitivity, which plays an important role in protecting against dietinduced obesity by suppressing appetite [39], is increased in Il1ra −/− mice. In this regard, it is interesting that leptin signalling in the CNS regulates energy expenditure via activation of the SNS, leading to BAT-like differentiation of WAT [40].…”
Section: Discussionmentioning
confidence: 78%
“…Non-selective agonists of the Mc3r and Mc4r suppress food intake and increase energy expenditure, primarily through Mc4r [8,28]. Cytokine stimulation of proopiomelanocortin neurons in the hypothalamus is thought to have an important role in weight loss associated with chronic illness [33]. Administration of antagonists of the Mc3r and Mc4r, or genetic blockade of Mc4r, are effective at ameliorating cachexia induced by bacterial endotoxin (lipopolysaccharide, or LPS) or cancer in several animal models [25,27,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…injection of IL-1 into the lateral ventricles activated expression of Fos protein in the ARC POMC neurons resulting in the inhibition of feeding behavior. In addition, IL-1 stimulated the release of -MSH from hypothalamic explants (Scarlett et al, 2007). Additionally, IL-1 has been shown to decrease secretion of AgRP from the hypothalamus (Scarlett et al, 2008).…”
Section: Wwwintechopencommentioning
confidence: 96%
“…It appears that central IL-1 signaling is required for the pharmacological, but not physiological, effects of leptin on energy balance (Wisse et al, 2007a). Recent studies have demonstrated that IL-1 suppresses appetite directly by the activation of central melanocortin system through its receptor IL-1RI abundantly expressed in neurons regulating appetite (DeBoer & Marks, 2006;Scarlett et al, 2007Scarlett et al, , 2008. The central melanocortin system forms the populations of POMC-and AgRP-expressing neurons in the ARC and the brainstem neurons in the nucleus tractus solitarius (Grossberg et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%